THE EFFECT OF GREEN MARKETING ON BRAND IMAGE AND PURCHASE DECISION (Study on Consumer of Starbucks Café Ubud, Gianyar Bali) - I Gusti Agung Nanda Dwipamurti; M. Kholid Mawardi; Inggang Perwangsa Nuralam (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This research aimed to (1) explaining the effect of Green Marketing toward Brand Image (2) explaining the effect of Green Marketing toward Purchase Decision, (3) explaining the effect of Brand Image toward Purchase Decision. The type of this research is explanatory research with quantitative approach. The variables of the research are Green Marketing, Brand Image, and Purchase Decision. The criteria of population in this research are (1) Respondent consumer with 18-35 years old, (2) Consumer of Starbucks Ubud or have ever purchase product at Starbucks Ubud, and (3) Respondent that understand about Starbucks Green Marketing. The sampling technique for this research was using purposive sampling and the data collection method by spreading questionnaire to 118 respondents according to population criteria. Data analysis used descriptive analysis and path analysis. The results showed that (1) Green Marketing has significant influence toward Brand Image, (2) Green Marketing has significant influence toward Purchase Decision, (3) and Brand Image has significant influence toward Purchase Decision. Kеywords: Green Marketing, Brand Image, Consumer Purchase Decision and Starbucks АBSTRАK Penelitian ini bertujuan untuk (1) menjelaskan pengaruh Pemasaran Hijau terhadap Citra Merek (2) menjelaskan pengaruh Pemasaran Hijau terhadap Keputusan Pembelian, (3) menjelaskan pengaruh Citra Merek terhadap Keputusan Pembelian. Jenis penelitian ini adalah explanatory research dengan pendekatan kuantitatif. Variabel penelitian adalah Pemasaran Hijau, Citra Merek, dan Keputusan Pembelian. Kriteria populasi dalam penelitian ini adalah (1) Responden konsumen dengan usia 18-35 tahun, (2) Pelanggan Starbucks Ubud atau pernah membeli produk di Starbucks Ubud, dan (3) Responden yang memahami tentang Starbucks Green Marketing. Teknik pengambilan sampel untuk penelitian ini adalah menggunakan purposive sampling dan metode pengumpulan data dengan menyebarkan kuesioner kepada 118 responden sesuai dengan kriteria populasi. Analisis data menggunakan analisis deskriptif dan analisis jalur. Hasil penelitian menunjukkan bahwa (1) Pemasaran Hijau memiliki pengaruh yang signifikan terhadap Citra Merek, (2) Pemasaran Hijau memiliki pengaruh yang signifikan terhadap Keputusan Pembelian, (3) dan Citra Merek memiliki pengaruh signifikan terhadap Keputusan Pembelian. Kаtа Kunci: Green Marketing, Brand Image, Consumer Purchase Decision dan Starbucks